Role of palladium crystallite size on CO oxidation over CeZrO 4-δ supported Pd catalysts - Burange, Anand S.; Reddy, Kasala Prabhakr; Gopinath, Chinnakonda; Shukla, Rakesh; Tyagi, Avesh K. (Journal of Molecular Catalysis, 2018)
Photodeposited palladium on nanocrystalline CeZrO 4-δ support was evaluated for CO oxidation, as a function of particle size and pre-treatment. All the catalysts were well characterized by XRD, SEM, EDX, TEM, CO chemi-sorption and Raman spectroscopy. It was observed that change in photodeposition time alters the average crystallite size of Pd, and the same was confirmed by CO chemisorption. 7 nm average crystallite size of Pd exhibited excellent catalytic activity for CO oxidation. In order to understand the effect of support and metal-support interaction, 1 wt% Pd was deposited deliberately onto reduced and oxidized CeZrO 4-δ support. The reduced support with anionic vacancies and more Ce 3+ species exhibited an improvement in CO oxidation at onset temperature. Detailed analysis shows that Pd-deposition occurs preferentially at oxygen-vacancy sites and subsequent metal-support interaction influences the catalysis.

Review on the recent advances in the design and structure–activity relationship of TiO2-based photocatalysts for solar hydrogen production - Mani, Sunesh S.; Rajendran, Sivaraj; Mathew, Thomas; Gopinath, Chinnakonda (Energy Advances, 2024)
The major issues that determine the efficiency of photocatalyst composite materials for solar hydrogen production, with or without a sacrificial agent, are efficient visible light harvesting properties, efficient separation of charge carriers and their utilization of redox sites, and stability. Thus, significant efforts have been devoted in the past few decades to modify the above characteristics by integrating constituent components of composites using different approaches. In the present review, we aim to summarize the recent advances, predominantly, in the area of TiO2-based photocatalyst composites for solar hydrogen production. Firstly, we present the recent progress in material integration aspects by discussing the integration of TiO2 with different categories of materials, including noble/3d metals, metal oxides/sulphides/selenides, other low bandgap semiconductors, C-based materials, and dye sensitizers. Furthermore, we discuss how material integration helps in tailoring the electronic and optical properties for activity tuning in solar H2 production. Subsequently, critical changes in the physico-chemical and electronic properties of composites with respect to their preparation methods, morphology, crystallographic facets, particle size, dopant, calcination temperature, and structure–activity relationship to solar hydrogen production are addressed in detail. Moreover, we discuss the importance of fabricating a photocatalyst in a thin film form and performing solar hydrogen production in different reactor set-ups for enhancing its photocatalytic performance, while addressing device scalability. Despite the significant advancements made in this field, solar-to-hydrogen conversion efficiency still needs to be improved to realise the practical application of solar hydrogen production. In this case, the direct conversion of water to hydrogen via overall water splitting and renewable H2 production from wastewater or biomass components by employing suitable photocatalysts are some possible ways to improve the energy efficiency, and continuous research in the above directions is highly desirable.